Application of musharakah mutanaqisah home financing as an alternative to traditional debt financing : lessons learned from the U.S. 2007 sub-prime crisis - Abdul Razak, Dzuljastri; Amin, Hanudin (2012)
One of the causes of the 2007 U.S. sub-prime crisis in 2007 is the use of traditional debt financing whereby the bank does not take risk of owning the property. Furthermore, the bank does not share its profit with customer and monthly instalment is pegged against market interest rate. This paper will initially examine salient issues (e.g. interest charges, indebtedness) faced by customers and banks during the crisis. Secondly, it will propose an alternative model known as musharakah mutanaqisah or diminishing partnership whereby the bank jointly own the property with customer and real rental rates replaces interest rate as a benchmark to the determine monthly instalment. In studying the rental rates, the hedonic pricing theory is discussed. It is argued that the musharakah mutanaqisah concept can address issues of the crisis through the application of the Shariah principles and necessary changes to the regulatory framework.